Group : how one therapist and a circle of strangers saved my life - Tate, Christie (Avid Reader Press, 2020)
A top law school graduate struggling with suicidal thoughts and an eating disorder describes her reluctant participation in a therapeutic support group that taught her the meaning of human connection and intimacy.